Validation of the Spin-T goniometer, a cervical range of motion device. - Agarwal S; Allison GT; Singer KP (Journal of Manipulative & Physiological Therapeutics, 2005)
OBJECTIVE: To test the validity of the Spin-T goniometer for the assessment of cervical range of movement. METHODS: A linear regression analysis for paired neck movements using first a foam head model and then human subjects was performed to quantify the differences between the measurements obtained from the MotionStar, a movement-tracking device, and the Spin-T. A within-subject repeated measures design using simultaneous data acquisition was completed. RESULTS: The coefficient of determination (R2) for all planes of cervical range of motion for both model and human data sets was higher than 0.99. The regression equations for the model data showed no significant (P > .05) intercept for flexion-extension and lateral rotation. Human data showed statistically significant intercept for flexion-extension (mean, -0.52 degrees) and lateral flexion (mean, 0.81 degrees) at P < .05. CONCLUSION: This study quantifies the difference between the MotionStar and the Spin-T goniometer and documents the systematic error between the measures. Where the error reached statistical significance, the magnitude of the error was very small (< 1.5 degrees). The results of this study suggest that the Spin-T goniometer may be used as a valid measuring instrument for cervical range of movement.